Interface gr?fica para redu??o de espectros ?pticos - Silva, Alberlan Lopes (2016)
This work shows the development of a graphical interface to reduce spectroscopic observations of peculiar galaxies present in the Catalogue of Southern Peculiar Galaxies and Associations (Arp and Madore 1987). The data have been observed with the Cassegrain spectrograph installed at the 1.6-m telescope of the Observat?rio do Pico dos Dias, Brazil/Laborat?rio Nacional de Astrof?sica ? Minist?rio da Ci?ncia Tecnologia e Inova??o (OOD/LNA-MCTI). The interface is called "PyOPD-Cass". In this project, the tasks present in IRAF package are sequenced together in order to produce calibrated data in flux and wavelength. Thus, the methodology used to reduce spectral data allows the user to quickly and easily insert all the necessary parameters for the spectral reduction process. The material developed in this work, within the concept of "pipeline", has the advantage of minimizing the time in the spectral reduction. As application of the computational process, we show only the spectral reduction to a selected set of 73 peculiar galaxies with emission lines observed over the long-term project carried out in OPD/LNA-MCTI ("Spectroscopic Study of Peculiar Galaxies and associations", OP2012A-009). The scientific results of these active galaxies will be discussed later in another study, already under development. All the development program was conducted in Python, further comprising PyRAF language and PyQt adapter as a basis for the final GUI architecture.